Program konseling hipotetik untuk mereduksi prokrastinasi akademik mahasiswa program studi bimbingan dan konseling UNIPA Surabaya - Ayong Lianawati (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
Academic procrastination of students can make lecturing process to be delayed.  This phenomenon often arises while students are required to be able to complete their academic tasks on time. The purpose of this research is to formulate a hypothetic program in addressing academic procrastination of students. The population of the research is students of guidance and Counseling Departement of UNIPA Surabaya school year 2018-2019. Collection data with techniques using  procrastination scale. The results showed from 117 students who underwent high-level procrastination of 38 students, moderate procrastination of 59 students, and low procrastination as much as 20 students, and the most dominant aspect is Emotional Distress (depressed when postponing tasks) as well as Perceived Ability (perception of ability). Hence the formulated counseling design focuses on developing self-efficacy and coping emotional of distress when working on tasks